The Vocabulary of Baltic-Finnish and Baltic Origin in the Russian Dialects of the Northwest - Мызников, Сергей А. А. (Slavistica Vilnensis, 2018)
[full article, abstract in Russian; abstract in Lithuanian and English] The problem of Baltic-Finnish, Baltic and Slavic (Russian) interaction has already been examined by us in various aspects: the differentiation of the Baltic-Finnish substratum in the North Russian dialects; the relationship of these Baltic and Baltic-Finnish origins in the Russian dialects of the Northwest; the Baltisms that are included in the Russian dialects through the medium of the Baltic-Finnish languages, etc. In this article, an attempt is made, on the basis of dialectal materials, to analyze the lexical units included in Russian dialects from the Baltic-Finnic languages with their final Baltsky source. The lexical data considered by us as lexemes of the Baltic-Finish origin are, in some cases, not native to this soil but represent earlier Baltic borrowings. These units of the Baltic-Finnish language continuum are its integral part; they often have a transformed form and semantics in comparison with the Baltic etymons. Later attempts were made either to expand or narrow the list of such units. Some of the lexemes of Baltic origin, being an integral part of the Baltic-Finnish continuum, had spread further to the North Russian dialects. This article gives examples of such mediated Baltics, which, due to the Baltic-Finnish nfluence, have spread widely in Russian dialects.